Memory and Identity in Documentary Video, The Case of Milpa Alta, Ciudad de México - Díaz Vázquez, María del Carmen (2019)
This work highlights the role of the documentary video in the preservation, recovery and dissemination of individual and collective memory from the voice of community actors. The proposal is inserted within the framework of an action research project in the towns of an urban-rural area of Mexico City: Milpa Alta. From the implementation of three workshops, oral tradition, memory and participatory documentary, the axes on which the story will be developed are established: community work, forest care and preservation of the Nahuatl language. In this way, the documentary video becomes a support for the transmission and dialogue of knowledge between generations, thus strengthening the sense of belonging of the inhabitants of native peoples, where tradition and modernity coexist.